THE EFFECTS OF VIDEO TUTORING ON ESP STUDENTS’ GRAMMAR MASTERY - Suparmi Suparmi (Celtic : A Journal of Culture, English Language Teaching, Literature and Linguistics, 2015)
The role of video as a medium of learning is believed to provide effects on students’ grammar mastery. However, since there are many kinds of video that can be used in different methods of learning, more studies are needed to provide evidence for determining the best methods of learning in the application of video. This research aims to investigate the effects of learning past and past continuous tense which use two different videos of learning - video tutoring and non-tutoring in two different English for Specific Purposes (ESP) classes. The research methodology utilized the t-test for independent samples. The results indicate that video tutoring had a great effect on the students’ grammar mastery. Lastly, practical and essential suggestions related to the result of the study, especially for language teachers and students, are discussed.